WAYS AND MEANS OF FORMING A LEGAL CULTURE IN MODERN UZBEKISTAN - Akhatovna, Ahmedshaeva Mavluda; Abdurashidovna, Mukhitdinova Firyuza (The journal of contemporary issues in business and government, 2021)
The article deals with the concept, structure and types of legal awareness. The work is devoted to the actual topic of the role and place of legal awareness in the democratization of public life. The authors studied a large amount of factual material on the formation and development of legal awareness in Uzbekistan, the main directions of the state's activities to improve legal awareness. Changes in the legislation and new requirements for the normative behavior of the individual are studied. The article highlights the problems of raising legal awareness as one of the main conditions for deepening democratic reforms.